Investigation of redox status in chronic cerebral hypoperfusion-induced neurodegeneration in rats - Saxena, Anil Kumar; Abdul Majeed, Saif Saad; Gurtu, Sunil; Mohamed, Wael M. Y. (Elsevier, 2015)
Aging related reduction in cerebral blood flow (CBF) has been linked with neurodegenerative disorders including Alzheimer's disease and dementia. Experimentally, a condition of chronic cerebral hypoperfusion due to reduced CBF can be induced by permanent bilateral occlusion of common carotid arteries (2-vessel occlusion, 2VO) in rats. Since oxidative stress, leading to neuronal apoptosis and death, is one of the mechanisms, which is thought to play a significant role in chronic degenerative neurological disorders, the present study was planned to assess the ROS status by measuring the levels of anti-oxidant enzymes that might occur during chronic cerebral hypoperfusion. Antioxidant enzymes namely glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase were measured in the brain tissue at eight weeks of 2VO induction in rats. Results show significantly elevated levels of GPx, SOD, and catalase enzymes as compared with the control group. It is possible that compensatory rise in antioxidant enzymes occurs in response to increased oxidative stress following ischemic insult.